Study of the Effect of Surfactants on the Determination of Gold by Flame Atomic Absorption Spectrometry - Pourreza, N.; Parham, H.; Elhami, Sh. (Asian Journal of Chemistry, 2016)
The effect of different surfactants on flame atomic absorption determination of gold is described. Various surfactants such as cetyltrimethyl ammonium bromide (CTAB), sodium dodecyl sulphate (SDS) and Brij-35 were investigated. All the surfactants enhanced the absorbance and the sensitivity of gold determination by flame atomic absorption. The degree of enhancement was higher for CTAB which has a charge opposite to that of anaIyte ion, since gold is present as AuCl4– or Au(NO3)4– in acidic solutions. The results showed that the reproducibility was increased by a factor of two in the presence of surfactants. The sensitivity (1 % absorption) was also improved by a factor of two.